EFFECTIVENESS OF ULTRASOUND EXAMINATION IN THE DIAGNOSIS OF PATHOLOGICAL PROCESSES OF THE MAXILLOFACIAL AREA IN CHILDREN - Tkachenko, P.I.; Bilokon, S.O.; Dolenko, O.B.; Buria, L.V.; Steblovskyi, D.V.; Korotych, N.M.; Makarenko, O.V. (World of Medicine and Biology, 2025)
In everyday clinical medical practice, there is a steady increase in the frequency of ultrasound examinations. We determined the effectiveness of its use in diagnosing pathological processes of the maxillofacial region based on the examination of 78 children aged 3 months to 17 years with various head and neck pathologies. The most significant number of ultrasound examinations was performed in patients with various nosological forms of lymphadenitis. As part of this work, 9 Doppler scans were performed. The results allow us to state that ultrasound examination, distinguished by its safety and effectiveness, is quite promising, requiring wider use in diagnosing and diagnosing diseases of the salivary glands, pathology of soft tissues of the maxillofacial region, lymph nodes, and vascular formations. Against its high informativeness, the possibility of some limitations of using diagnostic X-ray techniques and invasive diagnostic interventions and a more rational use of other radiation examination methods – computed tomography and magnetic resonance imaging – seems quite justified.
Keywords: children; ultrasound examination; Doppler ultrasonography; maxillofacial region; salivary glands; lymphadenitis; neck cysts